Alzheimer's disease - a review of medicinal substances and their derivatives - Marika Więcek; Dorota G. Piotrowska; Michał Kołodziejczyk; Iwona E. Głowacka (Polish Pharmaceutical Society, 2024)
Alzheimer's disease (AD) is a neurodegenerative disorder. Although the first case of Alzheimer's disease was recorded over a century ago, the etiology of the disease remains unknown. There are several hypotheses regarding the process of neurodegeneration, however, it is impossible to provide a specific cause of Alzheimer's disease in humans, due to the lack of in vivo models. Only a few specific changes in the body occurring in the course of this disease have been described so far, and no effective drugs have been developed to stop its progression. The effect of the currently used drugs is limited only to improving the cognitive functions and general patients' well-being. Four medicinal substances have been approved for the treatment of Alzheimer's disease so far, namely, donepezil, rivastigmine, galantamine, and memantine. In this article, a brief description of marketed drugs used for the treatment of Alzheimer's disease is presented as well as selected substances in phase III clinical trials. Moreover, a strategy of multifunctional ligands along with a description of the activity of selected compounds containing in their structure a moiety of one of the drugs used in the treatment of Alzheimer's disease, namely, donepezil, rivastigmine, or galantamine, is presented in the paper. Selected compounds synthesized over the last five years are described. Taking into account the multifactorial nature of Alzheimer's disease, the multifunctional ligands strategy directed at more than one biological target is used by many research groups. A large group of multi-target ligands is based on derivatives containing in their structure a moiety of selected acetylcholinesterase inhibitors. These moieties are combined with various types of compounds with known biological activity. As a result, derivatives with multi-target effects are obtained, mainly cholinesterase inhibitory properties and inhibition of the β-amyloid aggregation process, as well as antioxidant and neuroprotective effects.